Improving Human Resource Management for Sustainable Tourism Development in Local Government - Asmiatiningsih, Sri; Afrianti, Indah (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study aims to determine the ability of human resource management in the Department of Tourism, Youth, and Sports in the City of Bima. This study used a descriptive qualitative method. This research is located at the City of Bima's Tourism, Youth, and Sports Office; this location is very strategic in viewing case studies and problems. The subjects of this study were selected through a nonprobability sampling technique, using a purposive sampling technique or a sampling technique by considering specific aspects. Data collection techniques consist of observation, interviews, and documentation. The research results show that tourism activities have become a form of the service industry in the city of Bima. The reason for the importance of human resources in tourism management is that tourism activities cannot be carried out only by one person but must be carried out jointly by a group of people. In this case, the HR factor becomes a very crucial factor. Human resource management is critical, mainly so a company, agency, or organization can implement proper management to support quality. Placement of employee positions must also be based on educational background and academic qualifications in the field of work. Lack of human resource capacity with appropriate educational experience can be overcome by providing employee competency development programs, such as training, workshops, or academic capacity-building scholarships.